2002
DOI: 10.1084/jem.20020797
|View full text |Cite
|
Sign up to set email alerts
|

A Signal Peptide Derived from hsp60 Binds HLA-E and Interferes with CD94/NKG2A Recognition

Abstract: Human histocompatibility leukocyte antigen (HLA)-E is a nonclassical major histocompatibility complex (MHC) class I molecule which presents a restricted set of nonameric peptides, derived mainly from the signal sequence of other MHC class I molecules. It interacts with CD94/NKG2 receptors expressed on the surface of natural killer (NK) cells and T cell subsets. Here we demonstrate that HLA-E also presents a peptide derived from the leader sequence of human heat shock protein 60 (hsp60). This peptide gains acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(219 citation statements)
references
References 50 publications
(70 reference statements)
7
204
1
2
Order By: Relevance
“…This implies that the NKG2A ligand HLA-E, but not the KIR ligand HLA-C, is down-regulated in this system. Hsp60 has a leader sequence that binds HLA-E but is not permissive for recognition by NKG2A (40). However, we did not observe a change in the levels of hsp60 by Western blot (not shown).…”
Section: Vaccinia Virus Infection Induces Down-regulation Of Hla-ementioning
confidence: 44%
“…This implies that the NKG2A ligand HLA-E, but not the KIR ligand HLA-C, is down-regulated in this system. Hsp60 has a leader sequence that binds HLA-E but is not permissive for recognition by NKG2A (40). However, we did not observe a change in the levels of hsp60 by Western blot (not shown).…”
Section: Vaccinia Virus Infection Induces Down-regulation Of Hla-ementioning
confidence: 44%
“…However, Qa-1 can also bind other selfpeptides, including those derived from heat shock proteins (15) and preproinsulin leader sequences (16). In addition, human studies have shown that a signal peptide derived from the leader sequence of a stress protein Hsp60 (Hsp60sp) is capable of competing with the B7sp peptide, the human counterpart of Qdm, for occupancy of HLA-E, the human counterpart of Qa-1 (17). Interestingly, the resultant HLA-E/Hsp60sp complex does not interact with CD94/ NKG2A and therefore does not inhibit the NK activity.…”
Section: Resultsmentioning
confidence: 99%
“…21 In addition, HSPs can induce a polyclonal immune response and activate NK cells. 22,23 Thus, HSPbased vaccines emerge as promising strategy for immunotherapy. Accordingly, vaccination with autologous tumor-derived HSP-peptide complexes has been shown to result in both prophylactic and therapeutic antitumoral activity in a variety of animal models of cancer and several advanced clinical studies using autologous tumorderived HSPs are underway.…”
Section: Introductionmentioning
confidence: 99%